2022
DOI: 10.1039/d2tb00811d
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor-1 signaling pathway in macrophage involved angiogenesis in materials-instructed osteo-induction

Abstract: Although osteo-inductive materials are regarded as promising candidates for critical-sized bone repair, their clinical application is limited by ambiguous mechanisms. The hypoxia-inducible factor (HIF)-1 signaling pathway, which responds to hypoxic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…HIF-1α, which is one of the critical regulators of chondrocyte template formation, is stably expressed in a hypoxic environment, which sustains the survival of cells by altering cellular metabolism. HIF-1α was shown to largely contribute to the construction of vascular networks during bone repair, but the direct relationship between HIF-1α and osteoblast and osteogenic activity remains controversial [114,200]. Prolonged severe hypoxia was demonstrated to have severe adverse effects on bone formation and even a series of brutal outcomes, such as necrosis, which is in line with conventional understandings of cellular activity.…”
Section: Discussionmentioning
confidence: 79%
“…HIF-1α, which is one of the critical regulators of chondrocyte template formation, is stably expressed in a hypoxic environment, which sustains the survival of cells by altering cellular metabolism. HIF-1α was shown to largely contribute to the construction of vascular networks during bone repair, but the direct relationship between HIF-1α and osteoblast and osteogenic activity remains controversial [114,200]. Prolonged severe hypoxia was demonstrated to have severe adverse effects on bone formation and even a series of brutal outcomes, such as necrosis, which is in line with conventional understandings of cellular activity.…”
Section: Discussionmentioning
confidence: 79%
“…35 However, as a transcription factor, HIF-1ɑ can regulate the expression of a spectrum of angiogenic factors, which mainly affects angiogenesis indirectly by activating target genes related to angiogenesis. 36 Moreover, the skin tissue reaction results in vivo by histological studies was confirmed that with the increase of implantation time, the number of macrophages around the material increased sharply. It can be seen that the increasing gradient of silicon element content did not have a different effect on the number of macrophages, which may be because low concentrations of silicon ions have been able to stimulate the formation of macrophages.…”
Section: Effects Of Pais On Skin Tissue Reaction In Vivomentioning
confidence: 76%
“…Some researches show that VEGF is the principle pro‐angiogenic growth factor participating in the formation of blood vessel 35 . However, as a transcription factor, HIF‐1ɑ can regulate the expression of a spectrum of angiogenic factors, which mainly affects angiogenesis indirectly by activating target genes related to angiogenesis 36 . Moreover, the skin tissue reaction results in vivo by histological studies was confirmed that with the increase of implantation time, the number of macrophages around the material increased sharply.…”
Section: Discussionmentioning
confidence: 95%
“…Hypoxia-inducible factor (HIF)-1, a major and key factor mediating the mammalian hypoxia response, regulates the oxygen balance at the cellular, tissue, and biological levels [39]. Recent studies have shown that HIF-1 signaling pathway, which responds to hypoxic conditions, plays an important role in angiogenesis [40]. Endothelin is a peptide family containing three isoforms, EDN1, EDN2 and EDN3 [41], whose EDN1 can regulate vasoconstriction, affect cell proliferation, differentiation, migration, and apoptosis [42][43].…”
Section: Discussionmentioning
confidence: 99%